A systematic theory of argumentation : the pragma-dialectical approach - Eemeren, F. H. van (Frans Hendrik), 1946- (Cambridge University Press, 2004)
"In A Systematic Theory of Argumentation, two of the leading figures in argumentation theory, Frans H. van Eemeren and Rob Grootendorst, present a view of argumentation as a means of resolving differences of opinion by testing the acceptability of the disputed positions. Their model of a "critical discussion" serves as a theoretical tool for analyzing, evaluating, and producing argumentative discourse. In this approach, pragmatic and dialectical insights are combined by conceiving a critical discussion as a methodological exchange of speech acts between two parties." "A Systematic Theory of Argumentation is a major contribution to the study of argumentation and will be of particular value to professionals and graduate students in speech communication, informal logic, rhetoric, critical thinking, linguistics, and philosophy."--Jacket.